2015
DOI: 10.3758/s13414-015-1025-z
|View full text |Cite
|
Sign up to set email alerts
|

On the optimal viewing position for object processing

Abstract: Numerous studies have shown that a visually presented word is processed most easily when participants initially fixate just to the left of the word's center. Fixating on this optimal viewing position (OVP) results in shorter response times and a lower probability of making additional withinword refixations (OVP effects), but also longer initialfixation durations (an inverted-OVP or I-OVP effect), as compared to initially fixating at the beginning or the end of the word. Thus, typical curves are u-shaped (or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 76 publications
(143 reference statements)
1
8
1
Order By: Relevance
“…When readers do not fixate in this most convenient location, they are more likely to make a short fixation and then refixate the same word on their next saccade (see also Rayner, Sereno, & Raney, 1996). This is in contrast to the effects seen in single word recognition where a word is processed most rapidly when it is fixated at its center, at the optimal viewing location (OVL; e.g., McConkie, Kerr, Reddix, Zola, & Jacobs, 1989; Rayner et al, 1996; Vitu, O’Regan, & Mittau, 1990, but see O’Regan & Jacobs, 1992 and van der Linden & Vitu, 2016 who report a leftward bias). 1…”
contrasting
confidence: 64%
See 3 more Smart Citations
“…When readers do not fixate in this most convenient location, they are more likely to make a short fixation and then refixate the same word on their next saccade (see also Rayner, Sereno, & Raney, 1996). This is in contrast to the effects seen in single word recognition where a word is processed most rapidly when it is fixated at its center, at the optimal viewing location (OVL; e.g., McConkie, Kerr, Reddix, Zola, & Jacobs, 1989; Rayner et al, 1996; Vitu, O’Regan, & Mittau, 1990, but see O’Regan & Jacobs, 1992 and van der Linden & Vitu, 2016 who report a leftward bias). 1…”
contrasting
confidence: 64%
“…1. Research on object and scene perception echo these findings; viewers process isolated objects fastest when fixations are centrally located compared to more peripheral (Foulsham & Kingstone, 2013;van der Linden & Vitu, 2016), but viewers tend to undershoot the centers of objects embedded within a scene (Foulsham & Kingstone, 2013;Nuthmann & Henderson, 2010). 2.…”
Section: Fundingmentioning
confidence: 94%
See 2 more Smart Citations
“…At the object level, for example, recognition is known to be influenced by factors such as shape (e.g., Biederman, 1987 ; Biederman & Ju, 1988 ; Sharma, Gupta, & Malik, 2012 ) and orientation (Bartram, 1976 ; Lawson & Humphreys, 1996 ), as well as by the earlier-mentioned influences of color. In addition, studies of eye movement behavior have demonstrated an optimal viewing position for object recognition, whereby initial eye fixations are programmed to land on the center of a target object from the viewer’s point of gaze (Foulsham & Kingstone, 2013 ; Henderson, 1993 ; van der Linden & Vitu, 2016 ). In studies in which multiple 2-D images are presented within the same display, fixations to various objects will be planned using parafoveal information.…”
mentioning
confidence: 99%